2020
DOI: 10.1590/1678-992x-2018-0150
|View full text |Cite
|
Sign up to set email alerts
|

Production and nutritive value of pastures in integrated livestock production systems: shading and management effects

Abstract: This study aimed to evaluate the production characteristics of pastures in integrated livestock production systems. For that, an experiment was carried out in São Carlos, SP, Brazil, from 2013 to 2015. Forage development, production and nutritive value were evaluated in five beef cattle production systems: extensive continuous stocking (Urochloa decumbens) = EXT; intensive = INT; crop-livestock = iCL; livestock-forest = iLF and crop-livestock-forest = iCLF. Rotational stocking pastures in INT, iCL, iLF and iCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 17 publications
3
20
0
9
Order By: Relevance
“…The results found in this study are similar to those observed by Pezzopane et al. (2020), who performed a multivariate PCA approach of the growth characteristics, nutritional value and forage yield of Urochloa brizantha at different positions in the Eucalyptus urograndis understory, and found that increasing shading (positions closer to the tree rows) promoted a reduction in forage production. Similarly, Pezzopane et al.…”
Section: Discussionsupporting
confidence: 91%
“…The results found in this study are similar to those observed by Pezzopane et al. (2020), who performed a multivariate PCA approach of the growth characteristics, nutritional value and forage yield of Urochloa brizantha at different positions in the Eucalyptus urograndis understory, and found that increasing shading (positions closer to the tree rows) promoted a reduction in forage production. Similarly, Pezzopane et al.…”
Section: Discussionsupporting
confidence: 91%
“…Multivariate analysis is not widely applied in agricultural research, particularly in feed evaluation, however, our findings suggest that this oversight may underestimate the consequences of climate change for forage quality. Statistical ordination techniques like PCA can usefully reduce the complexity of large forage data sets, aiding interpretation (Gallo et al, 2013; Pezzopane et al, 2020) while also avoiding the issue of multiple comparisons posed by numerous univariate analyses and non-independence of the chemical constituents in individual plants. In this study, for tall fescue, the majority of variability under climate change treatments was first associated (PCA1) with nutritional parameters and secondarily (PCA2) associated with morphological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…have been greatly used due to the rapid growth after maize harvesting, increasing forage and animal production, and nutrient cycling. This cultivar has more response when rainfall conditions are favorable (rainy season), while B. ruziziensis and B. decumbens are most used in the offseason (less favorable water conditions) (Oliveira et al, 2019;Pezzopane et al, 2020). Moreover, common practice in grass-maize intercropping is the herbicide application (atrazine and nicosulfuron) in sub-doses for weed control and delay forage growth minimizing the competition with maize and reducing yield losses (Santos et al, 2015).…”
Section: Maize-grass Intercroppingmentioning
confidence: 99%
“…The spatial arrangement of trees in the agroforestry system mainly influences the understory microclimate conditions (Magalhães et al, 2020), reducing the temperature (Domiciano et al, 2018), wind speed (Karvatte Jr et al, 2016), and mainly photosynthetically active radiation (PAR) (Gomes et al, 2019;Nascimento et al, 2019). Thus, in agroforestry systems, especially in situations where there is an increase in shade levels near to the trees, a reduction in forage production has been reported (Gomes et al, 2019;Nascimento et al, 2019;Pezzopane et al, 2019;Pezzopane et al, 2020) and crop yield (Moreira et al, 2018;Pardon et al, 2018;Nardini et al, 2019). These factors are magnified when associated with water competition (Jose et al, 2004).…”
Section: Maize-forestry Intercroppingmentioning
confidence: 99%